AquaIndex development: Kick-off workshop - Ramachandran, Rohit (Institute for Global Environmental Strategies, 2024)
The WorldFish AquaIndex Kick-off Workshop served as a milestone event, bringing together a diverse group of stakeholders to lay the foundation for the development of a transformative tool designed to assess the sustainability of aquatic food systems. This AquaIndex is envisioned as a comprehensive and modular framework integrating economic, social, environmental, and governance indicators, addressing the multidimensional challenges faced by aquatic food systems globally. By leveraging innovative technologies, expert insights, and collaborative stakeholder engagement, the AquaIndex aims to provide actionable data and strategies that can guide policymakers, industry leaders, and local communities toward sustainable practices.